Mixed-methods study exploring health service access and social support linkage to the mental well-being of Canadian Indigenous pregnant persons during the COVID-19 pandemic - Gerald Giesbrecht; Jasleen Kaur; Lianne Tomfohr-Madsen; Catherine A Lebel; Jennifer Doyle; Sydney Levasseur-Puhach; Meghan Mollons; Lindsay Woods; Leslie Roos (BMJ Open)
Objectives This study aimed to explore how the unprecedented stressors associated with the COVID-19 pandemic may have contributed to heightened levels of depression and anxiety among pregnant Indigenous persons, and identify protective individual-level factors.Design The current study used a mixed-methods design including standardised questionnaires and open-ended response questions. Using hierarchical regression models, we examined the extent to which COVID-19-related factors of service disruption (ie, changes to prenatal care, changes to birth plans and social support) were associated with mental well-being. Further, through qualitative analyses of open-ended questions, we examined the coping strategies used by pregnant Indigenous persons in response to the pandemic.Setting Participants responded to an online questionnaire consisting of standardised measures from 2020 to 2021.Participants The study included 336 self-identifying Indigenous pregnant persons in Canada.Results Descriptive results revealed elevated rates of clinically relevant depression (52.7%) and anxiety (62.5%) symptoms among this population. 76.8% of participants reported prenatal care service disruptions, including appointment cancellations. Thematic analyses identified coping themes of staying informed, social and/or cultural connections and activities, and internal mental well-being strategies. Disruptions to services and decreased quality of prenatal care negatively impacted mental well-being of Indigenous pregnant persons during the COVID-19 pandemic.Conclusions Given the potential for mental well-being challenges to persist and long-term effects of perinatal distress, it is important to examine the quality of care that pregnant individuals receive. Service providers should advance policies and practices that promote relationship quality and health system engagement as key factors linked to well-being during the perinatal period for Indigenous persons.